Pathophysiology of Idiopathic Intracranial Hypertension - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2012)
Investigators at Emory University, Atlanta, GA review the epidemiology, pathophysiology and management of idiopathic intracranial hypertension (IIH), sometimes called pseudotumor cerebri or benign intracranial hypertension, terms now considered inappropriate.